Pengaruh Implementasi Manajemen Kurikulum Merdeka dan Strategi Mengajar Guru terhadap Peningkatan Karakter Siswa di SMKN 1 Sangatta Utara - Halimatus Sa’diyah; Eko Nursalim; Muh Ibnu Faruk Fauzi (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to determine the influence of the implementation of the Independent Curriculum management and teacher teaching strategies on improving student character at SMK Negeri 1 Sangatta Utara. This study was field research with a quantitative approach. Data collection techniques used questionnaires, observation, and documentation. The study population was all 230 11th-grade students at SMK Negeri 1 Sangatta Utara, with a sample of 115 respondents drawn using Suharsimi Arikunto's formula. Data analysis used multiple linear regression. The results showed that the implementation of the Independent Curriculum management had a significant effect on improving student character by 60.85%, while teacher teaching strategies had a 15.95% effect. The coefficient of determination (R²) of 0.768 indicates that the two independent variables together contributed 76.8% to student character improvement, while the remaining 23.2% was influenced by factors outside the study. Therefore, it can be concluded that the implementation of the Independent Curriculum management has a more dominant influence than teacher teaching strategies on student character development.